Junior High School Students’ Perception of Using Mobile Application to Learn English Pronunciation - Tasya Amanda Winzky; Aswir Aswir (Universitas Cokroaminoto Palopo, 2022)
Technology into their teaching as well as how to assist students in making use of resources such as media and the internet to improve their learning of all four skills, particularly teaching and learning English pronunciation. Students are gradually motivated by their personal learning needs, including those that arise from greater mobility and traveling activities, during the initial period of mobile learning. Mobile learning, particularly Mobile Assisted Language Learning (MALL), has become essential tools in the teaching and learning process as a result of this process. The purpose of this research is to look into junior high school students' perceptions of using a mobile app to learn English pronunciation. This study is an action research project that was carried out in one of Indonesia's Islamic Junior High Schools with first-grade students as participants (a total of 65 students). Data were collected through questionnaires and interviews. The results revealed that students perceived the use of mobile application in learning pronunciation positive and it can enhanceding the participants’ English pronunciation skills. The data analysis is shown by their positive feedbacks during the action implementation. The findings of this study suggest that various teaching media and tools be used to improve the English language skills of Junior High School students in the future. In this era, teachers are required to understand how to incorporate.